Umbilical cord blood: A promising source for allogeneic CAR-T cells - Liu, Dian-Dian; Hong, Wei-Cong; Qiu, Kun-Yin; Li, Xin-Yu; Liu, Yong; Zhu, Li-Wen; Lai, Wei-Xin; Chen, Han-; Yang, Hua-Qing; Xu, Lu-Hong; Fang, Jian-Pei (Frontiers in Oncology, 2022)
Antigen chimeric receptor T cell (CAR-T cell) therapy is an effective treatment for relapsed and refractory acute lymphoblastic leukemia (R/R ALL). However, autologous CAR-T cells derived from patients with B-ALL often show poor amplification ability, exhaustion, and anergy. To overcome this limitation, allogeneic CAR-T cells may be used as effective substitutes; however, which source would be the best substitute is unclear. In this study, we compared the immunophenotype and antitumor efficacy of anti-CD19 CAR-T cells derived from healthy donor cord blood, healthy donor peripheral blood (PB), and peripheral blood of B-ALL patients (PB (patient)) in vitro and NCG immunodeficient mice, respectively. The results revealed that CAR-T cells derived from healthy donor CB and PB showed a higher proportion of naïve T and central memory T cells and longer tumor suppression in tumor-bearing mice than those of PB (patient). PB (patient) CAR-T cells had a higher proportion of Treg cells and released high levels of IL-10, which also suggests a poor prognosis. Thus, CAR-T cells derived from healthy donors have better anti-tumor efficacy than CAR-T cells derived from PB (patient), and CB may be a good source for allogeneic CAR-T cells.